Financial Factors to Investment Decisions: The Mediating Role of Financial Behavior - Silfiani, Yeni; Senastri Dahlan, Kandi Sofia (Jurnal Indonesia Sosial Sains, 2023)
This study aims to investigate and analyze the influence of financial literacy, risk perception, and income on investment decisions through financial behavior as a mediating variable. The sampling technique employed in this research is non-probability sampling using the purposive sampling method. The sample consists of 223 respondents from generations X, Y, and Z in the Tangerang region who have previously made investments. The analysis method used is Partial Least Squares Structural Equation Modeling (PLS-SEM). The research findings indicate that financial literacy and income influence financial behavior. However, financial literacy and income do not directly impact investment decisions. Risk perception and financial behavior affect investment decisions. Income affects financial literacy. Financial behavior mediates the influence of financial literacy on investment decisions, and financial behavior also mediates the influence of income on investment decisions